Initiating Action Guru SKI dalam Mewujudkan Budaya Literasi di Madrasah Ibtidaiyah Kementerian Agama Kota Banda Aceh - Ira Maisyura; Hasan Basri; Zulfatmi Zulfatmi (Master's degree Department of Islamic Education Postgraduate Program of Universitas Islam Negeri (State Islamic University) Ar-Raniry, Banda Aceh in cooperation with Center for Research and Community Service (LP2M), 2022)
Madrasah Ibtidaiyah teachers have not all realized literacy-based learning. This is because teachers' initiating actions are not all very good, so an in-depth study is needed in this regard. The purpose of this study is to explain the literacy culture of SKI teachers and the initiating action of SKI teachers in shaping literacy culture in Madrasah Ibtidaiyah of the Ministry of Religious Affairs in Banda Aceh. This research is field research with descriptive analysis. The data were obtained from SKI teachers in Madrasah Ibtidaiyah in Banda Aceh. Data were collected by purposive sampling through questionnaires, observations, interviews, and documentation. Data analysis began with reducing data, displaying data, and constructing data interactively. includingThe results of this study show that the literacy culture of SKI teachers in Madrasah Ibtidaiyah is manifested through (1) daily activities, including reading activities 15 minutes before learning and reading the Quran; (2) weekly activities, including literacy every Saturday and Minimoli (Mini Moving Lybrary); (3) semesterly activities, including book summarizing programs, reading camps, book donations, book worms, book presentations, and story telling; and (4) annual activities, including making class libraries and hunting literacy programs. (good) forIn addition, the initiating action of SKI teachers in shaping a culture of literacy in Madrasah Ibtidaiyah of the Ministry of Religious Affairs in Banda Aceh City is divided into 3, namely a score of 50–70 (not good) for as many as 3 SKI teachers; a score of 71–80 (good) for as many as 8 SKI teachers; and a score of 81–100 (very good) for as many as 4 SKI teachers. Initiating action is not influenced by length of service, latest education, or school status but is determined by being responsive, acting independently, and doing more than required.